A escuta do equívoco na fala da criança: um impasse entre estrutura e função da língua (Listening to the error in the child’s speech: an impasse between structure and function of language) - Carvalho, Glória Maria Monteiro (2014)
This paper intends to bring into question the dichotomy structure vs function of language, based mainly on Michel Pêcheux. We tried to exemplify this discussion in the field of language acquisition. In such a field, there is a risk of excluding the singularity of the child's speech, sometimes denying the linguistic theory and sometimes applying this theory as a tool for the corpora description of these speeches. We assume that the investigator’s listening to the error in the child’s utterances indicates a point of impasse that, by capturing the investigator, questions the exclusive separation between structure and function of language, in the investigation on the linguistic trajectory of the child. KEYWORDS: Structure. Function. Impasse.